EFFECTS OF GLYCININ AND b -CONGLYCININ ON INTEGRITY AND IMMUNE RESPONSES OF MOUSE INTESTINAL EPITHELIAL CELLS - J. Xu; A. Zhou; Z. Wang; D. Ai (Journal of Animal and Plant Sciences, 2010)
Antigen protein contained in soybeans are the major cause of allergic reaction in young animals. In this study, glycinin and β-conglycinin were purified material and experimentally tested at concentration of 0.1, 5, and 10 mg/ml for their effects on integrity and immune responses of mouse intestinal epithelial cells. At 5 mg/ml or above, glycinin and β-conglycinin undermined the integrity of intestinal epithelial cells, inhibited epithelial cell proliferation, and significantly increase the levels of LDH and GOT released to the culture medium. The administration of glycinin and β-conglycinin also significantly promoted the secretion of inflammatory cytokines (IL-2, IL-6, IL-8), a key feature in allergic reactions.
Keywords: Glycinin; β-conglycinin; intestinal epithelial cells; integrity; cell factor